Social Media as a Political Platform in Africa: A Bibliometric Analysis - Hussein Gibreel Musa; Ana kumalasari; Alnour Abobaker Mohamed Musa (Universitas Muhammadiyah Yogyakarta, 2023)
This study employs bibliometric analysis to scrutinize the pivotal journals, institutions, and countries at the nexus of social media and political discourse in Africa. Utilizing VOSviewer, a dataset of 123 publications from 2013 to 2023 was culled from Scopus Database. The analysis encompasses diverse methodologies, each tailored to the specific nature of bibliometric investigation.